Kościół katolicki i neopogaństwo niemieckie w myśli Leona Halbana - Polak, Ryszard (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
This article presents the views of Leon Halban referring to the problems of German religiosity. In the first part of the article, the family and the character and the academic achievements of this scholar were characterized. In the next part of the article, his views on the role of the Catholic Church in European culture were analyzed and his position in which he made a critical assessment of German religiosity was presented. Halban assumed that the Christianity practiced by Germans since the Middle Ages did not result from their authentic conversion. The Germans were often religiously indifferent and tended to fall into various heresies and deviations from faith. They also sought to achieve supremacy of the state over the Church in public life and law. Halban argued that a renewal of morality can only be achieved in the Catholic Church, whose ethical principles and doctrine should be propagated and applied in everyday life.
Keywords: niemiecka religijność; historia; nazizm; neopoganizm; kościół katolicki; państwo